Dinâmica do sistema fluvial do Tocantins no trecho Marabá - Pedral de São Lourenço, Amazônia Oriental (PA) - CASTRO, Shirlen Cristina Nascimento de (2020)
This work completion course aims to geomorphological analysis and multitemporal (1984 and 2009/25 years) from the banks of the lower Tocantins. The Tocantins River basin has surface 379 774 km2, which represents 39.4% of the Tocantins-Araguaia River Basin, encompassing the states of Pará (19.4%), Maranhão (7.6%), Tocantins (46%), Goiás (26%) and Federal District (1%). Much of the basin is in the Midwest region of the country, where the source of the river, heading for the northern region, where its mouth in the Bay of Marajó. The section of this paper begins in the city of Marabá to Gatestone de São Lourenço, near St. Therese of the Tauri (Itupiranga-Pa), with a length of 104 km, for the purposes of the study it was decided to divide the river into three segments: Marabá, Itupiranga and Gatestone of São Lourenço. The methodology was based on: (1) literature search, (2) Acquisition of satellite images of the study area (Marabá, Itupiranga and Gatestone of São Lourenço), (3) processing of Landsat scenes (orbit-point: 223-64) sensor TM (Thematic Mapper), (4) generation of maps (geomorphological, geological, geomorphological change in the years 1984-2009 and multitemporal June-September 2009) using the ArcGIS 9.2. Set up six (6) morphological and morphometric variables, used as a benchmark during the research period. These variables were: length of channel sinuosity index, number of bars, bar area, number of islands and Islands area. Other indicators of change identified by morphometric analysis were measurements obtained sinuosity and channel extension, which provided distinct values in all segments for each historical period. The comparative geomorphological analysis of the three segments in 1984 and 2009 in Marabá, no significant changes in channel morphology. Identify with only minor variations in some quantitative parameters of islands and bars, which is natural considering that this is a river that carries abundant bottom load. Considering the average values of the coordinates of the channel to the station Itupiranga, the year 2009 has the highest average for the period, with 13,188 cm. The lowest average recorded refers to the period between 1984 and 194 cm, the sandy bars, had apparent mobility between 1984 and 2009. The segment Pedral of São Lourenço, is represented by chute and outcrops, there is rupture the bed inflict rightly by the predominance of rocky bottom, the channel presents-if a drainage pattern classified as rectilinear. With regard to multi-temporal behavior of the lower Tocantins in the months from June to September in 2009. In Marabá the number of islands ranged from thirteen (13) in (30/06) to fifteen (15) in (02/09). In times of flood and ebb, many times, these islands can migrate and / or expand. Segment Itupiranga on September 30 had five (5) bars that number increased to eight (8) on the 2nd of September, a total area of 13.1 km2. In Gatestone of São Lourenço (section 03), during the months of June and September of 2009, the area of the water body in June was 64.58 km2 with a decrease to 60.26 in September. Quota values on 30/06 increased from 553.5 to 254.5 in 02/09. Being lower values compared to those recorded in the month of June.